Eksekusi Objek Jaminan Fidusia Pasca Keluarnya Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 - Merry Arfiani (Universitas Nasional, 2022)
The execution of Fiduciary Guarantees is regulated in Articles 29 to 34 of the Law on Fiduciary Guarantees. Execution of Fiduciary Guarantee is the confiscation and sale of objects that are the object of the fiduciary guarantee due to the debtor's default or not fulfilling his performance on time to the creditor. The purposes of this research are: To find out and analyze the procedure for granting credit with fiduciary guarantees; To find out and analyze the position of the fiduciary guarantee in the event of a breach of contract; To find out and analyze the execution of fiduciary guarantees after the decision of the Constitutional Court Number 18/PUU-XVII/2019. The study method used in this paper is normative juridical, meaning that the law is conceptualized as what is written in the provisions of the Act or the law is conceptualized as a rule or norm which is a benchmark for human behavior that is considered appropriate. This normative legal study is based on primary and secondary legal materials, namely studies that refer to the norms contained in the provisions of the Act. The conclusion of this study is: the procedure for providing credit with a fiduciary guarantee is a series of activities that are correlated with each other to complete a job, namely channeling credit to parties who need financing. The existence of a credit granting procedure is applied to identify whether or not prospective debtors are given financing credits, so that the risk of bad loans can be cut as small as possible; The position of the fiduciary guarantee in the event of a breach of contract. The Fiduciary recipient has the right to take the object that is the object of the Fiduciary Guarantee and if necessary can request assistance from the competent authority. The execution of fiduciary guarantees after the Constitutional Court Decision Number 18/PUU-XVII/2019 provides a new interpretation of the constitution. Eksekusi Jaminan Fidusia diatur dalam Pasal 29 sampai dengan Pasal 34 Undang-Undang Tentang Jaminan Fidusia. Eksekusi jaminan fidusia adalah penyitaan dan penjualan benda yang menjadi objek jaminan fidusia dikarenakan debitor cidera janji atau tidak memenuhi prestasinya tepat waktu kepada kreditor. Tujuan penulisan dari penelitian ini adalah untuk mengetahui dan menganalisis prosedur pemberian kredit dengan jaminan fidusia; untuk mengetahui dan menganalisis kedudukan jaminan fidusia apabila terjadi cidera janji; untuk mengetahui dan menganalisis eksekusi jaminan fidusia setelah adanya putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019. Metode kajian yang dipakai dalam peulisan ini ialah yuridis normatif, artinya dimana hukum dikonsepkan sebagai apa yang tertulis dalam ketetapan Undang-Undang atau hukum dikonsepkan sebagai kaidah atau norma yang merupakan patokan berperilaku manusia yang dianggap pantas. Kajian hukum normatif ini didasarkan kepada bahan hukum primer dan sekunder, yaitu kajian yang mengacu pada norma-norma yang termaktub dalam ketetapan Undang-Undang. Kesimpulan dari kajian ini ialah: prosedur pemberian kredit dengan jaminan fidusia ialah serangkaian kegiatan yang saling berkorelasi guna menyelesaikan suatu pekerjaan yaitu menyalurkan kredit kepada pihak yang membutuhkan pembiayaan. Adanya prosedur pemberian kredit diaplikasikan guna mengidentifikasi layak atau tidaknya calon debitor diberikan kredit pembiayaan, sehingga resiko terhadap kredit macet dapat dipangkas sekecil mungkin; Kedudukan jaminan fidusia apabila terjadi cidera janji. Penerima fidusia berhak mengambil benda yang menjadi objek Jaminan Fidusia dan jika perlu dapat meminta bantuan pihak yang berwenang. Eksekusi jaminan fidusia setelah adanya Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 memberi tafsir baru terhadap konstitusi.